Menumbuhkan Minat Belajar Bahasa Inggris Anak Lewat Pelaksanaan PKL 2 di LKSA Anak Gembira - Debora Manalu; Erni Asneli Asbi (Yayasan Literasi Sains Indonesia, 2023)
This paper aims to find out the activities of implementing Field Work Practices carried out by Practitioners at LKSA Anak Gembira. Field Work Practice is one of the activities undertaken by final students in fulfilling assignments and practice during lectures. At this PKL, the practitioner will apply the PKL model in groups or it can be said that it is an effort to empower a group in overcoming their problems. The target to be achieved in this street vendor activity is to solve children's problems related to the lack of interest and interest in children in learning English, which often causes difficulties in following English lessons both at school and elsewhere. In addition, it was also reported that economic factors also contributed to the emergence of this problem, this is related to the high costs that will be incurred when choosing one type of English development tutoring. For this reason, in this street vendor activity, the practitioner also contributes to children by helping them overcome problems and come up with solutions and efforts to empower children. In this paper, we will describe some of the steps taken by a Social Worker in dealing with client problems and will obtain appropriate solutions and efforts to solve client problems.